THE NEED FOR INNOVATION IN TEACHER EDUCATION PROGRAMS IN THE 21ST CENTURY: BEST PRACTICES AND CHALLENGES IN CREATING INCLUSIVE CLASSROOMS - Man Mohan; Gupta, Tania (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Innovative teaching programs are necessary in the twenty-first century due to globalization, the quick development of technology, and the diversity of learner needs. This study looks at the pressing need to alter traditional teaching methods to educate educators for inclusive classrooms that value diversity and foster fair learning opportunities. It examines best practices such as the using digital resources, collaborative teaching methods, and differentiated instruction approaches that are essential for addressing the unique challenges of diverse learners. The research also lists resistance to change, a lack of resources, and a scarcity of teacher preparation as barriers to implementing innovative tactics. By addressing these concerns, teaching programs can equip teachers with the skills and mindset necessary to create inclusive, adaptable, and student-centered classrooms.